2004
DOI: 10.1090/s0002-9947-04-03688-8
|View full text |Cite
|
Sign up to set email alerts
|

Operators on $C(K)$ spaces preserving copies of Schreier spaces

Abstract: Abstract. It is proved that an operator T : C(K) → X, K compact metrizable, X a separable Banach space, for which the -Szlenk index of T * (B X * ) is greater than or equal to ω ξ , ξ < ω 1 , is an isomorphism on a subspace of C(K) isomorphic to X ξ , the Schreier space of order ξ. As a corollary, one obtains that a complemented subspace of C(K) with Szlenk index equal to ω ξ+1 contains a subspace isomorphic to X ξ .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Assertion (i) of Proposition 2.7 is a trivial generalisation of Lemma 2.7 of [13], requiring little change in the proof. Assertion (ii) is Lemma 2.8 of [13]. We refer the reader to [13] for the proofs.…”
Section: Treesmentioning
confidence: 95%
See 2 more Smart Citations
“…Assertion (i) of Proposition 2.7 is a trivial generalisation of Lemma 2.7 of [13], requiring little change in the proof. Assertion (ii) is Lemma 2.8 of [13]. We refer the reader to [13] for the proofs.…”
Section: Treesmentioning
confidence: 95%
“…Blossomed trees are used in [13] to study fixing properties of operators of large Szlenk index acting on C(K) spaces. The important property of a blossomed tree T in studying the Szlenk index is that for every t ∈ T \ MAX(T ) and cofinite subset…”
Section: Treesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then the Szlenk index has found a variety of uses in the study of Banach space geometry, a survey of which can be found in [14]. One of the main applications of the Szlenk index is in the study of C(K) spaces and their operators, as witnessed in particular by the work of Alspach [2], Alspach and Benyamini [1], Benyamini [3], Bourgain [5] and Gasparis [8]; we refer to the survey article [17] for a detailed discussion of this topic. The purpose of the current paper is to enlarge the class of C(K) spaces for which the Szlenk index of C(K) is known.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, one has an operator T : X → Y which is "large" in a suitable sense and tries to find a concrete object that the operator T preserves. Various versions of this problem have been studied in the literature and several satisfactory answers have been obtained; see, for instance, [1,4,5,13,14,15,16,23,24]. Among them, there are two fundamental results that deserve special attention.…”
Section: Introductionmentioning
confidence: 99%